An Overview of Blockchain Technology for Agro Transaction  - et. al., Mrs.NiroshiniInfantia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Public administration across worldwide with much increased resources demands transparency and security. As many countries started adopting smart city concepts, new technologies should be utilized to protect the several public administration services against corruption, intruders rendering active role and transparency for the public. The existing challenge of gaining trust, elimination of corruption can be achieved by integration of blockchain technology for the public administration process. The farmer personal, sensitive information’s are protected using Proof of Work (PoW) concept. Smart contracts can be utilized for the governmental subsidy money distribution to the farmers providing privacy preserving. This smart contracts can be helpful in eliminating over billing, money mishandling. The transparency is achieved by using hyperledger concept. To our knowledge this work is first public Blockchain based experimental approach for public administration compared with the theoretical approaches. This work study examines the impact of blockchain technology in agriculture benefiting the farmers eliminating the mediators, agents